Status of Gulayan Sa Paaralan (School Garden) Program in Public Elementary and Secondary Schools of Cawayan, Masbate, Philippines: Basis for Extension Activities - IBAÑEZ, ROGER; Velza, Jacob Frederick; Castillo, Iris; Bartolay, Riza (Future Science / FSH-PH Publications, 2022)
The Department of Education implemented gulayan sa paaralan (school garden) to assist the government in reducing malnutrition in the country. DEBESMSCAT-Cawayan Campus assessed the state of gulayan sa paaralan (school garden) of all public schools in Cawayan, Masbate as part of the evaluation technique to establish the suitable and needed extension services to be delivered. The study employed a descriptive research approach and purposive sampling. In the study, a structured survey questionnaire was used to collect data on the status of the gulayan sa paaralan (school garden) program in the schools. Data showed that the gulayan sa paaralan (school garden) initiative had not yet been adequately implemented for a variety of reasons. Schools utilized bolo to prepare the land, which took several months to complete. Planting supplies and other inputs were unavailable at all times, causing the output to be delayed. The lack of Department of Agriculture assistance for inputs, as well as the lack of training/seminars related to the gulayan sa paaralan (school garden) program, are factors that impede the program's implementation and sustainability. Since school heads did not appropriate funding from the MOOE, all coordinators were obliged to pull money from their purses to fund the gulayan sa paaralan (school garden) initiative. Due to low vegetable output, the gulayan sa paaralan (school garden) program in Cawayan public schools does not make a substantial contribution to combating school malnutrition. The implementing agency should explore a holistic strategy for GPP implementation in schools, with close collaboration with related agencies, stakeholders, and religious monitoring of the program should be strictly observed. The capacity of the school heads and coordinators to lead is a key element to the program's success.